PENINGKATAN KUALITAS PRODUK NORMAL NOODLE DENGAN MENGGUNAKAN METODE SIX SIGMA DAN FUZZY FMEA - Ririn Regiana Dwi Satya; Nurdeni Nurdeni (LPPM, 2022)
PT Indofood CBP Sukses Makmur Tbk is one of the companies engaged in the food sector, namely producing instant noodles. Preliminary research shows that PT Indofood Tbk Suskes Makmur Tbk has products that are not suitable and are formed as a result of sampling the production process, sometimes even exceeding the standards set by the company. The four production processes are cutting, frying, cooling and wrapping. In the four processes produced a number of different defective products, namely: In the cutting process the defective products produced were 30,586 pcs, in the frying process as many as 21,569 pcs, in the cooling process as many as 11,735 pcs and in the wrapping process as many as 42,000 pcs. %. In improving the quality, Six sigma and fuzzy FMEA methods are used. From the results of calculations using the conventional FMEA method and from the results of calculations with fuzzy logic for the value of FRPN using MATLAB software, it has different results, where the highest FRPN value is failure mode 1 (F1) or a risk factor for product defects because many noodle blocks are tucked away which can result in material wasteful with a value of 150 as a rating of 1. With this method, it is hoped that using the Six sigma method and fuzzy FMEA the company can improve quality and reduce the percentage risk of defects in the production process.